The Paratext of the Editions of Classical Roman Comedy Printed by Lazzaro de' Soardi as a 'Zone of Transaction'. - Torello-Hill, Giulia (Italian Studies, 2025)
This article examines the paratextual materials in Venetian editions of classical comedy published by Lazzaro de' Soardi between 1494 and 1515. His extensive activity as a printer of Terence's plays over a twenty-year period makes him an ideal case study to trace the development of the paratext in early sixteenth-century Venice. Through analysis of de' Soardi's business strategies, including printing privileges and strategic partnerships, this study argues that he pioneered the use of paratext as a 'zone of transaction' with his readership. De' Soardi introduced woodcut illustrations that provided visual cues on gestures and delivery, while his revolutionary use of the illustrated title page served as a sophisticated marketing tool. Additionally, a previously unnoticed note to the reader reveals important connections between printing trends and theatrical performances by the Compagnie della Calza, amateur troupes of young Venetian patricians, illuminating the interplay between textual production and performance culture in Renaissance Venice.